2014
DOI: 10.1563/aaid-joi-d-11-00127
|View full text |Cite
|
Sign up to set email alerts
|

Active Implant Periapical Lesions Leading to Implant Failure: Two Case Reports

Abstract: Implant periapical lesion (IPL), an inflammatory lesion surrounding the apex of a dental implant, has been previously reported as a possible cause for implant failure. This article describes 2 successive cases of active IPL that were diagnosed early by clinical signs and radiologic findings. Lesions were treated surgically with implant removal and debridement. The etiology, findings, and treatment approaches for IPL are discussed in comparison with other reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Our case involved the region of the upper left second premolar, corroborating Park et al, who state that IPL affects maxillary implants more than mandibular, predominantly in the premolar region [16]. The clinical signs associated with the x-ray findings provide information on IPL diagnosis [17]. IPL may be characterised by suppuration, formation of fistulas and loss of alveolar bone, however pain and fistula formation may not always be present [2,5].…”
Section: (C) the Lesion Is Observed Perforating The Vestibular Plate;supporting
confidence: 82%
See 3 more Smart Citations
“…Our case involved the region of the upper left second premolar, corroborating Park et al, who state that IPL affects maxillary implants more than mandibular, predominantly in the premolar region [16]. The clinical signs associated with the x-ray findings provide information on IPL diagnosis [17]. IPL may be characterised by suppuration, formation of fistulas and loss of alveolar bone, however pain and fistula formation may not always be present [2,5].…”
Section: (C) the Lesion Is Observed Perforating The Vestibular Plate;supporting
confidence: 82%
“…In a literature review, Romanos et al found that out of 32 reported cases of IPL, apicoectomy of the implant was carried out in 3 cases to gain access to the walls of the defect and allow complete debridement [19]; however in one of those cases the implant failed after apicoectomy. Other authors stress the importance of surgical debridement or the removal of sources of infection, including contaminated implants and apical lesions [17,22]. Buhara et al reported two clinical cases of implant failure due to IPL [17]; in both cases they decided to remove the implant and carry out very careful debridement in order to stop the rapid progression of the lesion and prevent damage to vital structures, promoting a definitive cure and resolving the patients' continuous pain.…”
Section: An Implant Periapical Lesion Associated With Presence Of Resmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve of the articles were excluded as they had no IOPAs of the lesion. 7,11,24,25,33,35,[37][38][39]45,48,53 A total of 54 IOPAs from 36 articles were compiled. One periodontist (SR) and one implantologist (TAB) independently analyzed the IOPAs.…”
Section: Literature Searchmentioning
confidence: 99%